Assessing Banking Sector Soundness in a Long-Term Framework : The Case of Venezuela - Blavy, Rodolphe (Washington, D.C. : International Monetary Fund, 2006)
This paper combines financial soundness indicators (FSIs) and stress-testing methodologies to provide a broad assessment of the soundness of Venezuela's banking sector, based on a diagnosis of its structural and transient shortcomings. While the Venezuelan banking sector appears sound under current favorable economic conditions, it remains significantly vulnerable to cyclical downturns-which have been severe in the past. Banks are particularly exposed to interest rate and credit risks. This suggests that the strong FSIs may be partly the result of a conjunctural credit boom in the context of capital controls and very low real interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet